2003
DOI: 10.1177/0011128702251054
|View full text |Cite
|
Sign up to set email alerts
|

A Classification of High-Risk Youths

Abstract: The authors report the results of developing and evaluating a classification of 315 arrested youths processed at the Hillsborough County Juvenile Assessment Center in Tampa, Florida. Cluster analysis of summary measures of nine baseline alcohol/other drug use and self-reported delinquency variables identified four groups of youths: (a) low-level delinquents and drug users, (b) high-level delinquents, (c) hair-test-identified marijuana and cocaine users, and (d) self-reported drug users. The validity of the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 21 publications
2
34
0
4
Order By: Relevance
“…In one study, high levels of delinquency were associated with higher rates of being neglected and physically abused, and higher rates of familial involvement in crime (Dembo and Schmeidler 2003). Other research, however, has found no significant difference in the total number of victimization experiences of delinquent and non-delinquent victims (Cuevas et al 2007).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In one study, high levels of delinquency were associated with higher rates of being neglected and physically abused, and higher rates of familial involvement in crime (Dembo and Schmeidler 2003). Other research, however, has found no significant difference in the total number of victimization experiences of delinquent and non-delinquent victims (Cuevas et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…The first goal was to describe how PTEs were reported in these evaluations and to compare the observed rates to those found in the broader juvenile justice population. Because higher levels of delinquency have been associated with higher rates of traumatic experiences in some studies (Dembo and Schmeidler 2003), and youth included in this study were charged directly in criminal court with relatively serious offenses, we expected rates of traumatic experiences to be similar to, or higher than, estimates of trauma in the juvenile justice population.…”
Section: The Current Study: Decertification In Pennsylvaniamentioning
confidence: 99%
“…For example, according to self-reports by delinquents institutionalized in a correctional facility, 24% fulfilled criteria for PTSD (Burton, Foy, Bwanaussi, Johnson, & Moore, 1994). From comprehensive psychological evaluations of 315 youth confined to an assessment center in the state of Florida, 22% scored above the clinical range for mental health problems (Dembo & Schmeidler, 2003). Steiner et al (1997) examined 205 delinquents who were under the supervision of the California Youth Authority and found that 16% were suffering from PTSD.…”
Section: Mental Health Childhood Maltreatment and Institutionalizedmentioning
confidence: 99%
“…It has also been shown that youths who experience alcohol and substance use are more likely to be involved in delinquency (e.g., Ellickson & McGuigan, 2000;Greenwood, 1992;Loeber, Green, Lahey, Frick, & McBurnett, 2000). Moreover, emotional and psychological functioning problems have been associated with delinquent behavior (e.g., Boesky, 2002;Dembo & Schmeidler, 2003;Teplin, Abram, McClelland, & Dulcan, 2002). Typically, risk assessments cover two or more of these risk domains (Schwalbe et al, 2006).…”
Section: Introductionmentioning
confidence: 99%